2020
DOI: 10.12738/jestp.2020.2.002
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Student School Burnout and Problematic Internet Use

Abstract: Student burnout and Internet addiction are two of the serious problems that are common among young people. Both are connected with many negative effects on the mental functioning of adolescents. However, so far only few studies have explored these two phenomena all together. The aim of our study was to test the relationship between student burnout (SB) and internet addiction (IA). Specifically, we explored three problems: (i) sex differences in the level of student burnout and problematic Internet use among Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…In Turkey, approximately 33 h were spent on the Internet per month in 2016 while 7.5 h (the world average of 6 h 43 min) were spent on the Internet a day and the most extensive use belonged to the 16-24 age group (90.7%), and that the usage ratio of Turkish adolescents is the highest in Europe (Atalan Ergin & Kapçı, 2019;Digital, 2020;TUİK, 2019TUİK, , 2020. It was also reported that most adolescents use the Internet for 2.17 ± 0.70 h a day on average, for 15 h a week and there is an advanced level difference between the Internet usage duration and Internet addiction and that men are more addicted but less aware of this situation (Batıgün & Hasta, 2010;Longstreet & Brooks, 2017;Tomaszek & Muchacka-Cymerman, 2020;Waldo, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Turkey, approximately 33 h were spent on the Internet per month in 2016 while 7.5 h (the world average of 6 h 43 min) were spent on the Internet a day and the most extensive use belonged to the 16-24 age group (90.7%), and that the usage ratio of Turkish adolescents is the highest in Europe (Atalan Ergin & Kapçı, 2019;Digital, 2020;TUİK, 2019TUİK, , 2020. It was also reported that most adolescents use the Internet for 2.17 ± 0.70 h a day on average, for 15 h a week and there is an advanced level difference between the Internet usage duration and Internet addiction and that men are more addicted but less aware of this situation (Batıgün & Hasta, 2010;Longstreet & Brooks, 2017;Tomaszek & Muchacka-Cymerman, 2020;Waldo, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Any deficiency in the acquisition of emotion regulation skills starting, which start in the early childhood and continuing to be shaped in the adolescence, weakens social development as well as increasing vulnerability against stress (Guyer et al, 2016; Modecki et al, 2017; Özdoğan & Cenkseven Önder, 2018). It is also stated that behavioral addictions related to the Internet emerge as a behavioral pattern used by the adolescent to transform negative mood into positive (Tomaszek & Muchacka‐Cymerman, 2020; Wang et al, 2018). Additionally, excessive occupation of adolescents with the Internet causes negative effects in terms of academic achievement performance and interpersonal relations, and this situation concerns parents (Chandrima et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Tomaszek and Muchacka-Cymerman (2020) found a significant but weak relationship between student school burnout and problematic internet use. Walburg et al (2016) revealed that the ‘exhausted from schoolwork’ dimension for girls and the ‘feelings of inadequacy at school’ dimension among boys are related to problematic Facebook use.…”
Section: Introductionmentioning
confidence: 88%
“…). This solution was tested and confirmed [73]. In their work, they distinguished such dimensions of Internet addiction as: Emotional and Cognitive Dependence (ECD), Time Management Problems (TMP), Lack of Control and Neglecting of Social Life, and Dishonesty about Internet Use (DI).…”
Section: Methodsmentioning
confidence: 99%